Coral Reef Condition in Popaya Island Waters, North Gorontalo - Matau, Moh Rizal N.; Katili, Abubakar Sidik; Hamidun, Marini Susanti; Ibrahim, Mustamim; Husain, Ilyas H.; Lamangantjo, Chairunnisah J. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This study aimed to describe the condition of coral reefs in the waters of Popaya Island, Mas Popaya Raja Nature Reserve, North Gorontalo Regency, using the Coral Point Count with Excel Extensions (CPCe) method. Data collection was conducted using the Underwater Photo Transect (UPT) method through skin diving along a 50-meter transect at a depth of 3–6 meters. Coral reef conditions were documented using a 60 × 40 cm frame placed alternately on the left and right sides of the transect line at one-meter intervals, resulting in 50 photographs. Data analysis was performed using 30 random points applied to each photograph to classify live and dead substrate categories. Environmental parameters, including water temperature, pH, current velocity, and water clarity, were also measured. The results showed that the environmental conditions of the waters supported coral growth, with a temperature of 28.7°C, pH of 7.8, current velocity of 0.51 m/s, and water clarity of 90%. The percentage of live coral cover was 74.37%, which was categorized as good. The composition of live coral cover was dominated by Acropora Branching (78.21%), followed by Coral Massive (12.34%), Acropora Tabulate (7.10%), and Coral Foliose (2.33%). The diversity index (H' = 1.41) and dominance index (D = 0.48) indicated a moderate category. The mortality index value of 0.10 indicated a low level of coral mortality. It can be concluded that the coral reef ecosystem in the waters of Popaya Island is in good and stable condition.